Testing of CFC targets by plasma heat fluxes relevant to ELMs and mitigated disruptions in ITER - Safronov, V.M.; Arkhipov, N.I.; Landman, I.; Strunnikov, V.M.; Toporkov, D.A.; Zhitlukhin, A.M. (Вопросы атомной науки и техники, 2006)
Carbon fibre composite (CFC) was irradiated by hot plasma streams at plasma gun facility MK-200UG. The CFC
targets were tested by plasma loads relevant to Edge Localised Modes (ELM) and mitigated disruptions in ITER. Onset
condition of CFC evaporation and properties of evaporated carbon were studied by use of infrared pyrometry and
visible spectroscopy.